Pendampingan Pemanfaatan Aplikasi Web Deteksi Dini Gejala Autisme Untuk Guru Paud Se Kabupaten Kotawaringin Timur - Jatmiko Wahyu Nugroho (CV. Era Digital Nusantara, 2024)
This community service aims to increase the capacity of PAUD educators in early detection of autism symptoms through assistance in utilizing the Autiso web application. This community service program uses the Participatory Action Research (PAR) method involving PAUD teachers in East Kotawaringin Regency as partners. The activities carried out include socialization, training, assistance in using the application, and evaluation of training results. The program results show that the Autiso application is effective in helping PAUD teachers conduct an initial assessment of autism symptoms in early childhood, especially in areas that have limited access to health workers. The evaluation of the program showed a high level of acceptance of the training materials and the Autiso application. The main obstacles faced were time constraints and coordination with partners spread across various sub-districts. The sustainability of this program is expected to be able to expand the use of the Autiso application to other schools in the region.